A Supersaturated Oxygen Emulsion for the Topical Treatment of Ocular Trauma. Issue 3 (21st December 2019) - Pate, Kathryn M; Goswami, Dinesh G; Lake, Mark; Lake, Sharon; Kant, Rama; Ammar, David; Tewari-Singh, Neera
Abstract: Introduction: Roughly 13% of all battlefield injuries include some form of ocular trauma. Ocular tissue preservation is critical for wound healing for warfighters with ocular injuries. Our team hypothesized that oxygen plays a vital role in ocular tissue preservation and wound healing and has developed a supersaturated oxygen emulsion (SOE) for the topical treatment of ocular trauma. Materials and Methods: The partial pressure of oxygen (PO2 ) was measured in the SOE. Safety and efficacy studies were carried out in primary human corneal epithelial (HCE) cells, as the outermost layer is the first barrier to chemical and mechanical injury. Western blot, scratch assay, and MTT assays were conducted to determine the effect of the SOE on various molecular markers, the rate of scratch closure, and cellular viability, respectively. Results: Data indicate that the SOE releases oxygen in a time-dependent manner, reaching a partial pressure within the emulsion over four times atmospheric levels. Studies in HCE cells indicate that application of the SOE does not lead to DNA damage, promote cell death, or hinder the rate of scratch closure and enhances cellular viability. Preliminary studies were carried out with chloropicrin (CP; developed as a chemical warfare agent and now a commonly used pesticide) as a chemical agent to induce ocular injury in HCE cells. CP exposures showed that SOE treatment reverses CP-induced DNA damage, apoptotic cell death, and oxidative stress markers. Conclusions: Maintaining adequate tissue oxygenation is critical for tissue preservation and wound repair, especially in avascular tissues like the cornea. Further studies examining the application of the SOE in corneal injury models are warranted.